Growth, yıeld and qualıty of some pearl mıllet [pennısetum glaucum (l.) R. Br.] Genotypes grown ın the semı-arıd clımate zone ın Türkiye (Bangladesh Journal of Botany, 2025)
This study was aimed to determine the performances of some pearl millet [Pennisetum glaucum (L.) R. Br.] genotypes that can be evaluated as roughage source in terms of forage yield and quality under second crop conditions. In this study, population number 3329, 4488, 5153, 8220, 9000, 9492, 9527, 10085 and 10467 and ‘White’ cultivars were used as plant material. Statistically significant differences were found among the genotypes in terms of plant height, number of stem, number of leaves on the main stem, green forage yield, hay yield, crude protein (CP), CP yield, acid detergent fiber, neutral detergent fiber and relative feed value. It was concluded that the highest agronomical productivity especially in terms of forage and CP yield was found in population number 4488.Bangladesh J. Bot. 54(2): 191-198, 2025 (June)